1975
DOI: 10.1037/h0077053
|View full text |Cite
|
Sign up to set email alerts
|

Passive avoidance behavior in rats after electroconvulsive shock: Facilitative effect of response retardation.

Abstract: Rats were trained in a one-trial passive avoidance task and then were submitted to electroconvulsive shock (ECS) or to sham ECS. Twenty-four hours later they were tested for retention,with the door opened either immediately or 30 sec after the beginning of the test. Rats initially forced to avoid for 30 sec continued to avoid for the entire test, but the others had the usual low step-through latencies seen withECS-treated animals. Activity measures for those animals stepping through differentiated groups havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the one-trial contextual fear paradigm, the animal receives a food shock upon the transition from a brightly lit large chamber into a smaller dark one (Sara et al, 1975; Ebenezer, 1988; Rudy and Sutherland, 1995; Rudy et al, 2004). If the animal is reintroduced to the big chamber, e.g., after a delay of 24 h, one finds that the animal avoids the normally preferred dark chamber.…”
Section: Animal Research On Episodic-like Memorymentioning
confidence: 99%
“…In the one-trial contextual fear paradigm, the animal receives a food shock upon the transition from a brightly lit large chamber into a smaller dark one (Sara et al, 1975; Ebenezer, 1988; Rudy and Sutherland, 1995; Rudy et al, 2004). If the animal is reintroduced to the big chamber, e.g., after a delay of 24 h, one finds that the animal avoids the normally preferred dark chamber.…”
Section: Animal Research On Episodic-like Memorymentioning
confidence: 99%
“…This was demonstrated in many studies showing recovery from ECS, hypoxia, or other experimentally induced retrograde amnesias. Effective "reminders" included a weak foot shock, exposure to the training context, or a combination of the training context and the foot shock Quartermain et al 1972;Miller and Springer 1972;Sara 1973;DeVietti and Hopfer 1974;Sara et al 1975;Gordon and Mowrer 1980). Small doses of analeptic drugs, such as strychnine, amphetamine, or piracetam, when administered before the retention test, also were shown to reverse ECS or hypoxiainduced amnesia, presumably by acting directly on retrieval processes (Sara and David-Remacle 1974;Sara and Remacle 1977).…”
Section: Retrieval Facilitation After Experimental Amnesiamentioning
confidence: 99%
“…In the 1970s, a series of important contributions by Spear (1973Spear ( , 1978 argued persuasively for the importance of retrieval deficits in many cases of forgetting, and studies by R. Miller (see Miller and Springer 1972) and others (Sara 1973;Sara et al 1975) showed that ECS-induced RA for new memory could also be viewed as a problem of retrieval rather than a loss of storage. Prominent among the findings was evidence that RA could be reversed or alleviated by reminder treatments, such as exposure to the context or training apparatus or to a noncontingent footshock prior to testing, as well as the demonstration that old memories could become vulnerable to amnesic agents following reactivation.…”
Section: A Retrieval-oriented Conceptmentioning
confidence: 99%